2019
DOI: 10.1016/j.ijrmhm.2019.104974
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, hardness and mechanical properties of two different unalloyed tantalum wires deposited via wire + arc additive manufacture

Abstract: An innovative way of producing large-scale unalloyed tantalum parts, based on the Wire + Arc Additive Manufacturing process, has been developed in this study. Two different unalloyed tantalum wires have been used to deposit 200-mm-long structures in tantalum. The effect of the wire chemistry on microstructure, hardness, porosity, mechanical properties and strain localisation has been investigated. The deposits showed high integrity and excellent mechanical properties, with yield strength, ultimate tensile stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The higher oxygen and nitrogen content in the coatings based on Ta, the greater the microhardness of the surface. This tendency is associated with the introduction of oxygen and nitrogen atoms into the tantalum crystal structure, what leads to compressive residual stress in the coatings [ 58 ]. In addition, the authors of work [ 59 ] found that the higher the oxygen content, the higher the average hardness.…”
Section: Resultsmentioning
confidence: 99%
“…The higher oxygen and nitrogen content in the coatings based on Ta, the greater the microhardness of the surface. This tendency is associated with the introduction of oxygen and nitrogen atoms into the tantalum crystal structure, what leads to compressive residual stress in the coatings [ 58 ]. In addition, the authors of work [ 59 ] found that the higher the oxygen content, the higher the average hardness.…”
Section: Resultsmentioning
confidence: 99%
“…Wire arc additive manufacturing (WAAM) is an emerging technology that is particularly suited to building large components through adding multiple layers of materials with the aid of an arc heat source, robotic manipulator and computer control. WAAM allows production of large components with medium resolution and surface quality [1], using a wide range of materials, such as steel [2,3], titanium alloy [4], nickel superalloy [5], aluminium [6], tantalum [7,8] and tungsten [9,10]. It was used for building a variety of components, from relatively simple walls [3] and cylindrical structures [11] to complex components with variable wall thicknesses, e.g., demo parts of turbine blades, wing spar and landing gear structures [11].…”
Section: Introductionmentioning
confidence: 99%
“…Copper alloys [19,39], nickel alloys [40][41][42], magnesium alloys [43,44], tantalum [45,46], tungsten [47,48] and high-temperature resistant MoNbTaWTi high-entropy alloy [49] produced in the WAAM process were also subjected to detailed analysis.…”
Section: Introductionmentioning
confidence: 99%